Geoturismo como elemento alternativo na economia de Feira de Santana - Bahia - Flores, Gladys Gregoria Pantoja (2022)
Geotourism seeks to integrate geodiversity with tourist activities to emphasize each place's identity, providing communities with tools for self-management and empowerment. Geotourism is science-oriented tourism, seeking to offer knowledge and have closer contact with geology and its areas of knowledge linked to the history or culture of the place, making leisure trips, or in the case of Feira de Santana de shopping, an educational enrichment for all ages. The municipality has an important road junction with six roads, which is an essential factor in urban expansion and directly influences the movement of people to this day. This municipality had its beginning connected to a determining factor: "water". Feira has dozens of lakes and important hydrographic basins, nothing more geological than this gigantic fluvial and lentic system. Feira de Santana is known for its commercial and gastronomic tourism, however it is considered as a city that has no aesthetic, cultural or natural attractions to offer. It can be interpreted that society attaches little importance or value to the goods it owns, despite being in a geographically privileged location. This research tries to study the possibilities of Geotourism in the medium or long term, as an alternative element and value aggregator in the economy of the locality, making known elements of its geodiversity to the population, through inventorying and quantification of geosites and/or site of geodiversity, in addition to a semi-quantitative assessment of ex situ geodiversity.This work also seeks to rescue memories to help conserve significant constructions that mark an era. This work aimed, through geotourism, to add geoscientific knowledge to the assets that the municipality has, making an evaluation and description of the assets, as well as the identification of the diversity of rocks and materials used in the buildings, facades, monuments and churches, which offers knowledge of how these elements were used. In this research, the final result was the Geotouristic model of Feira de Santana, indicating points and trails. It concluded with the presentation of two (geo)tourist macro sets: i) urban routes, close to municipal commerce, such as the famous “Feiraguay”, an open-air resale area of ​​various imported products, only matched by Feiras de Brasília and on the 25th of March in São Paulo. ii) and distant routes, for nature observation and cultural experiences, which will probably be in a second moment, for the development of local tourism and for those who are willing to know the municipality initially named as “Olhos D'Água", “princesinha do sertão ”, which has its origin in strong and fighting women, such as Maria Quitéria - the name of one of its districts. This is a contribution in the scientific community to the studies of geotourism, the registration and inventory of geosites and/or geodiversity sites (enriching the Geossit platform), which can be potentially attractive to (geo)tourists, which can strengthen the rediscovery of the historical and cultural heritage linked to Geosciences that is part of the city's identity, and thus encourage, in the population, a sense of belonging to places that offer much more than aesthetic and scenic or commercial values.